SOMA 2013 : proceedings of the 17th Symposium on Mediterranean Archaeology, Moscow, 25-27 April 2013 - Fazlullin, Sergei; Antika, Mazlum Mert (Access archaeology., 2015)
This volume presents papers from the 17th Symposium on Mediterranean Archaeology, SOMA 2013, held in Moscow, 25-27 April 2013.